Structural connectivity associated with familial risk for mental illness: A meta‐analysis of diffusion tensor imaging studies in relatives of patients with severe mental disorders. Issue 9 (14th March 2022) - Xu, Mengyuan; Zhang, Wenjing; Hochwalt, Paul; Yang, Chengmin; Liu, Naici; Qu, Jiao; Sun, Hui; DelBello, Melissa P.; Lui, Su; Nery, Fabiano G.
Abstract: Schizophrenia (SCZ), bipolar disorder (BD), and major depressive disorder (MDD) are heritable conditions with overlapping genetic liability. Transdiagnostic and disorder‐specific brain changes associated with familial risk for developing these disorders remain poorly understood. We carried out a meta‐analysis of diffusion tensor imaging (DTI) studies to investigate white matter microstructure abnormalities in relatives that might correspond to shared and discrete biomarkers of familial risk for psychotic or mood disorders. A systematic search of PubMed and Embase was performed to identify DTI studies in relatives of SCZ, BD, and MDD patients. Seed‐based d Mapping software was used to investigate global differences in fractional anisotropy (FA) between overall and disorder‐specific relatives and healthy controls (HC). Our search identified 25 studies that met full inclusion criteria. A total of 1, 144 relatives and 1, 238 HC were included in the meta‐analysis. The overall relatives exhibited decreased FA in the genu and splenium of corpus callosum (CC) compared with HC. This finding was found highly replicable in jack‐knife analysis and subgroup analyses. In disorder‐specific analysis, compared to HC, relatives of SCZ patients exhibited the same changes while those of BD showed reduced FA in the left inferior longitudinal fasciculus (ILF). The present study showed decreased FA in the genu and splenium of CC in relatives of SCZ, BD, and MDD patients, which might represent a shared familial vulnerability marker of severe mental illness. The white matter abnormalities in the left ILF might represent a specific familial risk for bipolar disorder. Abstract : To characterize whether there are common and disorder‐specific genetic contributions to white matter integrity in individuals at increased familial risk for developing psychiatric disorders, we carried out a meta‐analysis including 25 prior diffusion tensor imaging studies in relatives of patients with schizophrenia, bipolar disorder, and major depressive disorder. Results showed that overall relatives of the three disorders exhibited reduced fractional anisotropy in the genu and splenium of the corpus callosum, which might represent shared familial vulnerability marker of severe mental illness.